Three-dimensional multi-scale electrode with nanosheet microstructure and preparation method thereof

Three-dimensional multi-scale electrodes with a micro-structure with nanocrone microcontroller through electrochemical assisted acid etching-alkali growth, which solves the problem of low catalytic activity and stability of existing electrical catalysts. Catalytic performance and stability.

CN119372700APending Publication Date: 2025-01-28NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411491287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing electrocatalysts have low catalytic activity during the electrolysis process of hydrogen production, and catalyst falls off easily under long-term testing or high-current working conditions, resulting in a decrease in performance and stability.

Method used

The electrochemical auxiliary acid etching-alkali growth two-step legal system preparation with a three-dimensional multi-scale electrode with a microstructure of nano tablets is used to regulate the electrochemical process of the electrochemical on the surface of the electrode through the circulating volt-stroke and linear scanning voltanos.

Benefits of technology

Improving the catalytic performance of the electrode in the electrolytic aquatic oxygen reaction, increasing the number of surface area and active sites, improving the stability and applicability of the electrode, and suitable for industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372700A_ABST
    Figure CN119372700A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional multi-scale electrode with a nanosheet microstructure and a preparation method of the three-dimensional multi-scale electrode, and relates to the field of electrode preparation. Taking the alloy sample block as a working electrode, placing the working electrode in an acid solution for electrochemical acid etching, and adjusting the peak voltage of the working electrode relative to a reference electrode, the voltage change speed of the working electrode, the loading time interval and the number of cycles to control the electrochemical acid etching process so as to obtain a three-dimensional multi-scale electrode intermediate; taking a three-dimensional multi-scale electrode intermediate as a working electrode, placing the working electrode in an alkali solution for alkali growth, and adjusting the peak voltage of the working electrode relative to a reference electrode, the voltage change speed of the working electrode, the loading time interval and the number of cycles so as to control the growth speed and the distribution uniformity of the obtained nanosheets; and washing and drying to obtain the three-dimensional multi-scale electrode. By controlling the microstructure of the micro-nano structure on the surface of the electrode, the catalytic performance of the electrode in the water electrolysis oxygen generation reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode preparation, in particular to a three-dimensional multi-scale electrode with a nanosheet microstructure and a preparation method thereof. Background Art

[0002] Water electrolysis is a key technology for green hydrogen production. Its zero-carbon emission hydrogen production process will provide a guarantee for the development of a low-carbon society in the future. Direct water electrolysis to produce hydrogen consumes a lot of energy and has low electrolysis efficiency. The development of efficient electrocatalysts to promote water dissociation, reduce energy consumption, and improve efficiency is the current research trend in the field of water electrolysis to produce hydrogen.

[0003] The electrocatalytic water splitting process consists of two half reactions, namely the 2-electron hydrogen production reaction (HER) and the 4-electron oxygen production reaction (OER). The four-electron process of OER requires higher energy consumption, and the electrolyte solution is locally in an oxidizing environment during the reaction, which is more likely to cause catalyst oxidation and reduce reaction performance. In addition, most electrocatalysts are currently in powder form, and they need to be coated on carriers such as nickel foam and carbon paper during testing to achieve the electrocatalytic oxygen production effect. However, under long-term testing or high-current working conditions, the catalyst is very likely to fall off, resulting in a significant decrease in its performance and stability. The flaked powder particles will also pollute the electrolyzer and its solution system, making it difficult to meet commercial needs.

[0004] In recent years, three-dimensional porous metal-based integrated electrodes have attracted attention due to their good structural stability and regular pore size characteristics. However, directly manufactured metal-based electrodes do not have a micro-nanostructured surface, resulting in low catalytic activity. In order to improve the catalytic OER performance, high-activity components of precious metals are often loaded, including methods such as electrodeposition or impregnation. Acid-base liquid phase etching can also be used to construct micro-nano surfaces and expose active sites in the substrate.

[0005] For example, the Chinese invention patent with application number 202110134183.6 discloses a porous NiCu nanoneedle array catalyst and a preparation method thereof. The patent specifically discloses the preparation of NiCu master alloy strips, which are used as working electrodes in a three-electrode system and placed in a 0.5MH 2 SO 4Electrochemical etching was performed to obtain porous NiCu, the etching voltage was 1.0V (vs.Ag / AgCl), the etching time was 300s, and then the obtained porous NiCu was connected to the electrochemical workstation as the working electrode in the three-electrode system, and placed in 1MKOH for anode activation, the activation voltage was 0.6V (vs.Ag / AgCl), and the activation time was 400s, that is, a porous NiCu nanoneedle array catalyst that can be used as an electrode material to catalyze the electrolysis of water to produce hydrogen was obtained. Although the electrode material prepared by this method has a nanoneedle-like micro-nano structure, its average particle size is as high as ~500nm, so its specific surface area is still smaller than that of the nanosheet structure, which limits the number of catalytic active sites exposed on the surface of the structure, resulting in limited improvement in the catalytic hydrogen production performance during the electrolysis of water. In addition, this method uses constant voltage etching, and cannot accurately control the structural changes on the electrode surface, making it difficult to achieve large-scale promotion and application. Summary of the invention

[0006] The present invention aims to provide a three-dimensional multi-scale electrode with a nanosheet microstructure and a preparation method thereof, so as to improve the catalytic performance of the electrode in the electrolysis of water to produce oxygen by controlling the microscopic morphology of the micro-nanostructure on the electrode surface.

[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing a three-dimensional multi-scale electrode with a nanosheet microstructure, comprising the following steps:

[0008] S1: Preparation of alloy specimens;

[0009] S2: The alloy sample block is used as the working electrode, Ag / AgCl is used as the reference electrode, and the carbon rod is used as the counter electrode. The three-electrode system is connected through an electrochemical workstation and placed in an acid solution for electrochemical acid etching. The electrochemical acid etching adopts cyclic voltammetry, and the electrochemical acid etching process is controlled by adjusting four parameters in the cycle waveform: the peak voltage E1 of the working electrode relative to the reference electrode, the voltage change speed V1 of the working electrode, the loading time interval T1, and the number of cycles N1.

[0010] S3: cleaning and drying the alloy sample after electrochemical acid etching to obtain a three-dimensional multi-scale electrode intermediate;

[0011] S4: A three-dimensional multi-scale electrode intermediate is used as the working electrode, Ag / AgCl is used as the reference electrode, and a carbon rod is used as the counter electrode. The three-electrode system is connected through an electrochemical workstation and placed in an alkaline solution for alkaline growth. The alkaline growth adopts linear sweep voltammetry. The growth rate and distribution uniformity of the nanosheets obtained by alkaline growth are controlled by adjusting four parameters in the cyclic waveform: the peak voltage E2 of the working electrode relative to the reference electrode, the voltage change rate V2 of the working electrode, the loading time interval T2, and the number of cycles N2.

[0012] S5: cleaning and drying the three-dimensional multi-scale electrode intermediate after the alkali growth to obtain the three-dimensional multi-scale electrode.

[0013] As a further optimization of the above technical solution: the adjustment range of the four parameters in electrochemical acid etching is: the peak voltage E1 of the working electrode relative to the reference electrode is 1-2V, the voltage change rate V1 of the working electrode is 50-200mV / s, the number of cycles N1 is 10-100 circles, and the loading interval time T1 is 1-30s.

[0014] As a further optimization of the above technical solution: the adjustment range of the four parameters in alkali growth: the peak voltage E2 of the working electrode relative to the reference electrode is 1-2.5V, the voltage change rate V2 of the working electrode is 10mV / s, the number of cycles N2 is 100-1000, and the loading time interval T2 is 1-5min.

[0015] As a further optimization of the above technical solution: in step S2, the acid solution is a sulfuric acid aqueous solution with a concentration of 0.5 mol / L.

[0016] As a further optimization of the above technical solution: in step S4, the alkaline solution is a potassium hydroxide aqueous solution with a concentration of 1-5 mol / L.

[0017] As a further optimization of the above technical solution: the preparation method of the alloy sample block is: according to the required metal active site type, the corresponding metal / alloy powder is selected, and at the same time, a sacrificial metal is selected according to the electrochemical corrosion potential, the sacrificial metal powder and the metal / alloy powder are mixed to obtain a powder raw material, and then the powder raw material is melted at a high temperature in an argon atmosphere or prepared by 3D printing to obtain the alloy sample block.

[0018] As a further optimization of the above technical solution: the mass ratio of each element in the alloy sample block is Fe:Co:Ni:Cr:Al=17.5:19.7:38.2:16.1:8.5.

[0019] As a further optimization of the above technical solution: in step S3, the alloy sample after electrochemical acid etching is washed with deionized water, placed in an oven at 80° C. for 24 hours for drying, and a three-dimensional multi-scale electrode intermediate is obtained.

[0020] As a further optimization of the above technical solution: in step S5, the three-dimensional multi-scale electrode intermediate after alkali growth is washed alternately with deionized water and ethanol, and placed in an oven at 80° C. for 24 hours to obtain the three-dimensional multi-scale electrode.

[0021] A three-dimensional multi-scale electrode with a nanosheet microstructure is prepared by the above preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] In the preparation method of the present invention, firstly, the alloy sample block is electrochemically acid-etched to dissolve the metal with a lower potential in the sample block, and a three-dimensional porous structure is generated on the smooth surface of the alloy sample block. In the electrochemical acid etching, by controlling the number of different etching cycles and the cycle waveform, the etched metal and its etching rate can be accurately controlled to make its microscopic morphology more uniform; secondly, when the acid-etched alloy sample block is subjected to alkaline growth in an alkaline solution, by applying a peak voltage, controlling the concentration of the alkaline solution and the number of linear voltammetry cycles, the metal sites exposed on the surface after acid etching contain sufficient hydroxide in the alkaline solution, which promotes the hydroxide reaction in the solution to reconstruct the in-situ growth of the nanosheet structure. If a constant voltage is used to treat the sample in an alkaline solution, it is difficult to control the reconstruction growth process of the sample surface.

[0024] The growth process of nanosheets includes the diffusion process of metal ions. Too high or too low metal ion concentration will lead to uneven and unstable surface nanostructures. The present invention adopts a cyclic loading method to regulate the dissolution, diffusion and deposition process of each metal ion and hydroxide ion on the sample surface. During the cyclic loading process, when the voltage increases, the metal on the sample surface dissolves. At this time, the metal ion concentration around the sample increases and diffuses to the external solution. When the voltage drops or stops, the metal ion concentration remains unchanged, while maintaining diffusion to the external solution. When the concentration is equivalent, it no longer diffuses; when the metal ion concentration accumulates to a certain extent, it is deposited in a solution environment with sufficient hydroxide ions to form a nanosheet structure on the sample surface. Therefore, through the preparation method of the present invention, the nanosheet structure can be reconstructed in situ without adding the corresponding metal ions in the solution environment. The growth process of the nanosheet can be accurately controlled by the waveform and the number of cycles, so as to achieve strong bonding and uniform growth of the nanosheet and the substrate.

[0025] The present invention realizes precise control of acid etching and nanosheet growth through cyclic loading and controlling the waveform of the loading curve. Since both acid etching and nanosheet growth require the diffusion of ions, it is found through linear cyclic loading that controlling the etching time by different waveforms can effectively provide uniform diffusion time of ions. Therefore, the preparation method of the present invention can effectively inhibit local excessive corrosion or growth of the alloy sample block, thereby improving the uniformity of the microstructure of the electrode surface.

[0026] The present invention processes the alloy sample block by a two-step electrochemically assisted acid etching-alkaline growth method, accurately controls the smooth surface of the alloy sample block, and prepares the surface of the alloy sample block into a micro-nano scale multi-level structure composed of a nanosheet-porous substrate. The treated alloy sample block serves as a three-dimensional multi-scale electrode with a larger specific surface area and more active sites, has excellent catalytic performance in the alkaline electrolysis of water oxygen production reaction, can be directly assembled into an alkaline electrolytic cell for use, is suitable for industrial production, and reduces manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the principle of the three-dimensional multi-scale electrode preparation method;

[0028] Figure 2 It is a process flow chart of the three-dimensional multi-scale electrode preparation method;

[0029] Figure 3 Electrochemical window control for acid etching: a. Schematic diagram of cycle waveform control parameters; b. Schematic diagram of solution concentration changes during acid etching;

[0030] Figure 4 Electrochemical window control for alkali growth: a. Schematic diagram of cycle waveform control parameters; b. Schematic diagram of solution concentration change; c. Schematic diagram of nanosheet surface reconstruction thickness;

[0031] Figure 5 The SEM morphology of the surface of the alloy sample block after acid etching: a. Non-uniform etching under constant voltage; b. Uniform etching morphology obtained by cyclic loading waveform;

[0032] Figure 6 The SEM morphology of the alloy sample after alkali growth: a. Untreated morphology; b. Non-uniform structure obtained under constant voltage; c. Uniformly distributed nanosheet microstructure obtained by cyclic loading;

[0033] Figure 7 Comparison of specific surface area between nanosheet structure and nanorod structure: a. Surface nanosheet structure of cyclically loaded sample; b. Nanorod structure after treatment with prior art; c. Specific surface area distribution of nanosheet structure; d. Specific surface area distribution of nanorod structure;

[0034] Figure 8 Oxygen production from water electrolysis of untreated samples, samples treated with constant voltage, and samples treated with cyclic controlled waveform: a. LSV curve, b. Current density of 500 mA cm -2 Overpotential comparison bar graph;

[0035] Fig. 9 XRD spectra of eutectic dual-phase high entropy alloy: untreated sample, constant voltage treated sample and cyclic controllable waveform treated sample;

[0036] Fig.10 The element energy dispersive X-ray spectrum (EDX) of the three-dimensional multi-scale electrode surface prepared in Example 1;

[0037] Fig.11 Schematic diagram of sample structure change during chemical assisted acid etching-alkaline growth process;

[0038] Fig.12 Schematic diagram of the device for the electrochemically assisted acid etching-alkaline growth process. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.

[0040] The present invention discloses a method for preparing a three-dimensional multi-scale electrode with a nanosheet microstructure. In the preparation method, the device used in the electrochemical assisted acid etching-alkaline growth process is as follows: Fig.12 The principle of the preparation method is as shown in Figure 1 As shown, the process flow of the preparation method is as follows Figure 2 shown.

[0041] The specific steps are as follows:

[0042] S1: Preparation of alloy specimens;

[0043] Specifically, the preparation method of the alloy sample block is as follows: according to the required metal active site type, the corresponding metal / alloy powder is selected, and at the same time, a sacrificial metal is selected according to the electrochemical corrosion potential, the sacrificial metal powder and the metal / alloy powder are mixed to obtain a powder raw material, and then the powder raw material is melted at high temperature in an argon atmosphere or prepared by 3D printing to obtain the alloy sample block.

[0044] In electrochemical reactions, different metal elements are suitable for different reactions. For example, for alkaline water electrolysis to produce oxygen, the commonly used transition metals are iron, cobalt, and nickel metals, while for acidic water electrolysis to produce oxygen, metals such as chromium, manganese, cobalt, ruthenium, and iridium are often required. Therefore, different types of metal powders can be selected and mixed and smelted according to needs to prepare corresponding electrode sample blocks for processing. Similarly, for the selection of sacrificial metals, more active metal aluminum powders are often selected, which are easier to peel off during acid corrosion and construct microstructures.

[0045] Different metals have different potentials. When metals come into contact with electrolytes, a potential difference will appear, causing electron flow in the solution, so that the metal with low potential will be corroded first. For example, when the peak voltage is 1.0V, 0.5MH 2 SO4 In solution (pH = 1), Fe is oxidized to Fe 3+ , Co is Co 2+ , and when the peak voltage is 0.5V, Fe will be oxidized to Fe 2+ , Co is Co 2+ . Similarly, for alloy phases, the corroded phase can also be controlled by controlling the applied peak potential E. The sacrificial metal can be considered as an element that is easier to be etched, while the active site metal is an element that plays a catalytic role in the catalytic process. Taking the iron-cobalt-nickel-chromium-aluminum (FeCoNiCrAl) high entropy alloy as an example, the Al element is easier to be corroded, so Al is a sacrificial metal, and the remaining retained phase provides catalytic activity, so the active site metal of the FeCoNiCrAl high entropy alloy is FeCoNiCr.

[0046] S2: An alloy sample block is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode. The three-electrode system is connected through an electrochemical workstation and placed in an acid solution for electrochemical acid etching. The acid solution is a sulfuric acid aqueous solution with a concentration of 0.5 mol / L. The electrochemical acid etching adopts cyclic voltammetry, and the electrochemical acid etching process is controlled by adjusting four parameters in the cyclic waveform: the peak voltage E1 of the working electrode relative to the reference electrode, the voltage change rate V1 of the working electrode, the loading time interval T1, and the number of cycles N1. The adjustment range of the four parameters in the electrochemical acid etching is: the peak voltage E1 of the working electrode relative to the reference electrode is 1-2V, the voltage change rate V1 of the working electrode is 50-200mV / s, the number of cycles N1 is 10-100, and the loading interval time T1 is 1-30s.

[0047] S3: cleaning and drying the alloy sample after electrochemical acid etching to obtain a three-dimensional multi-scale electrode intermediate;

[0048] S4: A three-dimensional multi-scale electrode intermediate is used as the working electrode, Ag / AgCl is used as the reference electrode, and a carbon rod is used as the counter electrode. A three-electrode system is formed by connecting them through an electrochemical workstation and placed in an alkaline solution for alkaline growth. The alkaline solution is an aqueous potassium hydroxide solution with a concentration of 1-5 mol / L. The alkaline growth adopts linear sweep voltammetry. The growth rate and distribution uniformity of the nanosheets obtained by the alkaline growth are controlled by adjusting four parameters in the cyclic waveform: the peak voltage E2 of the working electrode relative to the reference electrode, the voltage change rate V2 of the working electrode, the loading time interval T2, and the number of cycles N2. The peak voltage E2 of the working electrode relative to the reference electrode is 1-2.5 V, the voltage change rate V2 of the working electrode is 10 mV / s, the number of cycles N2 is 100-1000, and the loading time interval T2 is 1-5 min.

[0049] S5: cleaning and drying the three-dimensional multi-scale electrode intermediate after the alkali growth to obtain the three-dimensional multi-scale electrode.

[0050] It should be noted that among the four key control parameters introduced in the present invention: whether etching is started is controlled by the peak voltage of the working electrode relative to the reference electrode, which is the etching threshold; the voltage change rate controls the speed and degree of single growth; the loading time interval controls the solution ion diffusion time, thereby affecting the uniformity of the overall etching; the number of cycles controls the number of uniform etching growths, thereby controlling the overall etching degree; the etching process is more accurately controlled by the four key control parameters.

[0051] For the alkali growth process, the peak voltage of the working electrode relative to the reference electrode is the threshold of alkali growth, which controls whether the alkali growth is started; the voltage change rate controls the speed and degree of single growth; the loading time interval controls the solution ion diffusion time, which in turn affects the uniformity of the overall growth; the number of cycles controls the number of uniform growths, thereby controlling the overall growth degree, and more accurately controlling the growth process. Thus, the nanosheet growth process is more accurately controlled through four key control parameters.

[0052] Example 1

[0053] This embodiment discloses a method for preparing a three-dimensional multi-scale electrode with a nanosheet microstructure. The specific preparation method is as follows:

[0054] (1) Using eutectic Fe-Co-Ni-Cr-Al high entropy alloy powder raw material, a eutectic alloy metal cylinder with a diameter of 50 mm and a height of 30 mm was prepared by high-temperature argon smelting, and an alloy sample block with a length, width and thickness of 10 mm × 10 mm × 1 mm was prepared by cutting;

[0055] (2) preparing a 0.5 mol / L aqueous solution of sulfuric acid;

[0056] (3) In the above solution, an alloy sample block is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected through an electrochemical workstation to form a three-electrode system;

[0057] (4) In a three-electrode system, the alloy sample block is subjected to controllable electrochemical acid etching by cyclic voltammetry; Figure 3 As shown, the peak voltage E1 of the working electrode relative to the reference electrode Ag / AgCl is set to 2V, the voltage change rate V1 of the working electrode is 50mV / s, the number of cycles N1 is 10, and the interval time T1 is 1s.

[0058] (5) After the acid etching is completed, the sample is washed with deionized water three times and placed in an oven at 80°C for 24 h to obtain a three-dimensional multi-scale electrode intermediate;

[0059] (6) preparing a potassium hydroxide aqueous solution with a concentration of 1 mol / L;

[0060] (7) In an alkaline potassium hydroxide aqueous solution, the three-dimensional multi-scale electrode intermediate is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected by an electrochemical workstation to form a three-electrode system;

[0061] (8) In an alkaline three-electrode solution system, chromium-aluminum-doped iron-cobalt-nickel hydroxide nanosheets were grown in situ on the sample surface by linear sweep voltammetry, such as Figure 4 As shown, the peak voltage E2 of the working electrode relative to the reference electrode Ag / AgCl is set to 2.5V, the voltage change rate V2 of the working electrode is 10mV / s, the number of cycles N2 is 100, and the interval time T2 is 1min;

[0062] (9) The treated samples were washed alternately with deionized water and ethanol for several times and dried in an oven at 80 °C for 24 h to obtain a three-dimensional multi-scale electrode with a nanosheet microstructure.

[0063] Example 2

[0064] This embodiment is the same as steps (1) to (4) of embodiment 1, except that:

[0065] (5) In a three-electrode system, the alloy sample block is subjected to controllable electrochemical acid etching by cyclic voltammetry; the peak voltage E1 of the working electrode relative to the reference electrode Ag / AgCl is set to 1 V, the voltage change rate V1 of the working electrode is set to 200 mV / s, the number of cycles N1 is set to 100, and the interval time T1 is set to 30 s.

[0066] (5) After the acid etching is completed, the sample is washed with deionized water three times and placed in an oven at 80°C for 24 h to obtain a three-dimensional multi-scale electrode intermediate;

[0067] (6) preparing a potassium hydroxide aqueous solution with a concentration of 5 mol / L;

[0068] (7) In an alkaline potassium hydroxide aqueous solution, the three-dimensional multi-scale electrode intermediate is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected by an electrochemical workstation to form a three-electrode system;

[0069] (8) In an alkaline solution three-electrode solution system, chromium-aluminum doped iron-cobalt-nickel hydroxide nanosheets were grown in situ on the sample surface by linear sweep voltammetry, the peak voltage E2 of the working electrode relative to the reference electrode Ag / AgCl was set to 1 V, the voltage change rate V2 of the working electrode was set to 10 mV / s, the number of cycles N2 was 800, and the interval time T2 was 5 min;

[0070] (9) The treated samples were washed alternately with deionized water and ethanol for several times and dried in an oven at 80 °C for 24 h to obtain a three-dimensional multi-scale electrode with a nanosheet microstructure.

[0071] Example 3

[0072] This embodiment is the same as steps (1) to (4) of embodiment 1, except that:

[0073] (5) In a three-electrode system, the alloy sample block is subjected to controllable electrochemical acid etching by cyclic voltammetry; the peak voltage E1 of the working electrode relative to the reference electrode Ag / AgCl is set to 1.5 V, the voltage change rate V1 of the working electrode is set to 100 mV / s, the number of cycles N1 is set to 80, and the interval time T1 is set to 15 s.

[0074] (5) After the acid etching is completed, the sample is washed with deionized water three times and placed in an oven at 80°C for 24 h to obtain a three-dimensional multi-scale electrode intermediate;

[0075] (6) preparing a potassium hydroxide aqueous solution with a concentration of 2.5 mol / L;

[0076] (7) In an alkaline potassium hydroxide aqueous solution, the three-dimensional multi-scale electrode intermediate is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected by an electrochemical workstation to form a three-electrode system;

[0077] (8) In an alkaline solution three-electrode solution system, chromium-aluminum doped iron-cobalt-nickel hydroxide nanosheets were in situ grown on the sample surface by linear sweep voltammetry, the peak voltage E2 of the working electrode relative to the reference electrode Ag / AgCl was set to 1.5 V, the voltage change rate V2 of the working electrode was set to 10 mV / s, the number of cycles N2 was 1000, and the interval time T2 was 2.5 min;

[0078] (9) The treated samples were washed alternately with deionized water and ethanol for several times and dried in an oven at 80 °C for 24 h to obtain a three-dimensional multi-scale electrode with a nanosheet microstructure.

[0079] Comparative Example 1

[0080] This comparative example is step (1) of Example 1: specifically, a eutectic iron-cobalt-nickel-chromium-aluminum high entropy alloy powder raw material is used to prepare a eutectic alloy metal cylinder with a diameter of 50 mm and a height of 30 mm by high-temperature smelting in argon gas, and an alloy sample block with a length, width and thickness of 10 mm×10 mm×1 mm is prepared by a cutting method.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 1 and Example 1 is that, in the process of preparing the electrode in this comparative example, constant voltage loading is adopted for both electrochemical acid etching and alkaline growth.

[0083] Specific:

[0084] (1) Using eutectic Fe-Co-Ni-Cr-Al high entropy alloy powder raw material, a eutectic alloy metal cylinder with a diameter of 50 mm and a height of 30 mm was prepared by high-temperature argon smelting, and an alloy sample block with a length, width and thickness of 10 mm × 10 mm × 1 mm was prepared by cutting;

[0085] (2) preparing a 0.5 mol / L aqueous solution of sulfuric acid;

[0086] (3) In the above solution, an alloy sample block is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected through an electrochemical workstation to form a three-electrode system;

[0087] (4) In a three-electrode system, the relative reference electrode voltage is set to 2 V, and the alloy sample block is subjected to constant voltage electrochemical acid etching;

[0088] (5) After the acid etching is completed, the sample is washed with deionized water three times and placed in an oven at 80°C for 24 h to obtain an electrode intermediate;

[0089] (6) preparing a potassium hydroxide aqueous solution with a concentration of 1 mol / L;

[0090] (7) In an alkaline potassium hydroxide aqueous solution, the three-dimensional multi-scale electrode intermediate is used as a working electrode, Ag / AgCl is used as a reference electrode, and a carbon rod is used as a counter electrode, which are connected by an electrochemical workstation to form a three-electrode system;

[0091] (8) In a three-electrode solution system of alkaline solution, the relative reference electrode voltage is set to 2.5 V to allow in-situ alkaline growth to occur on the surface of the sample;

[0092] (9) The treated sample was washed alternately with deionized water and ethanol for several times, and dried in an oven at 80°C for 24 h to obtain an electrode.

[0093] Comparative Examples 3-8

[0094] The overall steps of Comparative Examples 3-8 are the same as those of Example 1, except that the specific values ​​of the four adjustment parameters are different during the acid etching and alkaline growth processes:

[0095] Next, the performance of the products obtained in Example 1 and Comparative Examples 1-8 were tested.

[0096] Experimental methods:

[0097] The products of Comparative Example 1, Comparative Example 2, and Example 1 are respectively recorded as Sample 1, Sample 2, and Sample 3;

[0098] With sample 1, sample 2, and sample 3 as working electrodes, carbon rod as auxiliary electrode, and Ag / AgCl electrode as reference electrode, LSV test was carried out in 1 M KOH alkaline solution in a voltage window of 0.5-2.5 V and a scanning rate of 5 mV / s (compensating for solution internal resistance), and the initial current data was converted into current density.

[0099] Experimental results analysis:

[0100] The overpotentials of the three samples were analyzed, such as Figure 8 As shown in b, the current density is 500 mA cm -2 When the overpotentials of the three samples are: Sample 1: 514mV; Sample 2: 397mV; Sample 3: 280mV. It can be seen that the overpotentials of the treated samples 2 and 3 are lower than those of the initial sample 1, and the overpotential of sample 3 is reduced by about 30% after the cyclic loading treatment.

[0101] The oxygen production performance of water electrolysis of the three samples was analyzed. Figure 8 a shows the LSV curves of oxygen production from electrolyzed water of the three samples. It can be seen that the oxygen production performance of the treated samples 2 and 3 is improved compared with the initial sample 1, and the improvement of sample 3 is more significant after the cyclic loading treatment.

[0102] The present invention processes the alloy sample block by a two-step electrochemically assisted acid etching-alkaline growth method, accurately controls the smooth surface of the alloy sample block, and prepares the surface of the alloy sample block into a micro-nano scale multi-level structure consisting of a nanosheet-porous substrate, such as Fig.11 As shown, after acid treatment, the alloy sample obtains a groove-type macrostructure of micrometer scale, and then after alkali treatment to grow nanosheets, a micro-nano scale multi-level structure of nanosheet-porous substrate is obtained.

[0103] In order to further analyze the role of acid etching and alkaline growth in the present invention, the intermediate products and final products in the preparation process of Example 1, Comparative Example 1 and Comparative Example 2 were tested and analyzed:

[0104] Figure 5 The SEM morphology of the samples after acid etching is shown: 5a is the non-uniform etching under constant voltage, i.e., the electrode intermediate in Comparative Example 2; 5b is the uniform etching morphology obtained by cyclic loading waveform, i.e., the three-dimensional multi-scale electrode intermediate in Example 1. Figure 5It can be seen that the surface etching degree obtained by constant voltage acid treatment is different and the uniformity is poor, while the cyclic loading acid treatment shows more uniform grooves, achieving controllable etching of the sample surface.

[0105] Figure 6 The SEM morphology of the sample after alkali growth is shown in Figure 6a, which is the untreated morphology, i.e., the alloy sample block of Comparative Example 1; Figure 6b is the non-uniform structure obtained under constant voltage, i.e., the electrode obtained in Comparative Example 2; and Figure c is the uniformly distributed nanosheet microstructure obtained by cyclic loading, i.e., the three-dimensional multi-scale electrode with nanosheet microstructure obtained in Example 1. Figure 6 It can be seen that the surface micro-nanostructure of the sample obtained under constant voltage conditions has agglomeration phenomenon, while the surface nanostructure of the sample obtained through the cyclic loading process is more uniform and dense. This is because during the growth process of the alkaline solution, the cyclic loading method can regulate the dissolution, diffusion and deposition process of each metal ion and hydroxide ion on the surface of the sample. During the cyclic loading process, when the voltage increases, the metal on the surface of the sample dissolves. At this time, the concentration of metal ions around the sample increases and diffuses into the external solution. When the voltage decreases or at the stop time, the concentration of metal ions remains unchanged, while diffusion into the external solution is maintained. When the concentration is equivalent, it no longer diffuses. When the concentration of metal ions accumulates to a certain extent, deposition occurs in a solution environment with sufficient hydroxide ions, forming hydroxide nanosheets on the surface.

[0106] The surface nanosheet structure of the sample obtained in Example 1 was observed by scanning electron microscopy, and its specific surface area was estimated, as shown in FIG. Figure 7 As shown, the nanosheet is approximated as a two-dimensional image, and its specific surface area can be obtained by the approximate ratio of the circumference and area of ​​the nanostructure. By counting the nanostructures in the global area of ​​the electron microscope image, the columnar distribution diagram of the specific surface area of ​​each nanosheet and the average specific surface area are estimated to be 0.211. Compared with the prior art (application number 202110134183.6), the same method is used to measure its nanocolumnar structure, and the average specific surface area of ​​its nanocolumns is about 0.019, which is less than 1 / 10 of the nanosheet structure. Therefore, the nanosheet structure obtained by this method has a higher specific surface area, which can provide more active sites for the reaction, so as to significantly improve the catalytic performance.

[0107] By observing the morphological characteristics of comparative examples 3-10 during the electrode preparation process and after preparation, it was found that after acid etching of comparative example 3-6, the surface etching degree of the intermediate obtained was different and the uniformity was relatively general. The micro-nano structure distribution on the electrode surface of comparative examples 7-10 after alkaline growth was uneven, and there was agglomeration of micro-nano structures to varying degrees.

[0108] Further detection of the overpotential of the electrode obtained in Comparative Examples 3-10, analysis of the test results found that the overpotential of Comparative Examples 3-10 was lower than the initial sample, but higher than the electrode obtained in Example 1, indicating that in the acid etching and alkali growth process, the adjustment of the peak voltage, voltage change rate, number of cycles, and interval time affects the overpotential size. This is because the change of any of the four parameters will affect the morphological characteristics of the micro-nano structure on the electrode surface, and to a certain extent affect the degree of reduction of the overpotential. The lower the overpotential, the easier it is for the electrode to drive the electrochemical reaction under the same conditions, which means that the catalytic activity of the electrode is higher. It can be seen from this that in the process of preparing a three-dimensional multi-scale electrode with a nanosheet microstructure, the change of any of the four parameters will affect the catalytic performance of the electrode and the oxygen production performance of the electrode when electrolyzing water to produce oxygen. Only by using the parameter adjustment method of the present invention can the local excessive corrosion or growth be effectively suppressed, the uniformity of the nanosheet microstructure on the electrode surface be improved, and better water electrolysis oxygen production performance be achieved.

[0109] In addition, the treated electrodes were subjected to phase analysis ( Fig. 9 ), it was found that the main phase was still the alloy phase, indicating that the structure only underwent surface structural reformation and its bulk structure was very stable. Since the raw material for preparing the alloy sample block was the eutectic Fe-Co-Ni-Cr-Al high entropy alloy powder, the components in the formed nanosheets still contained Fe-Co-Ni-Cr-Al. The corresponding surface energy spectrum element analysis was as follows Fig.10 The surface atomic mass ratio is shown in the following table:

[0110] In summary, the alloy sample was treated by electrochemically assisted acid etching-alkaline growth cycle loading to successfully construct an integrated electrode with a three-dimensional multi-scale micro-nano surface structure, and exhibited extremely high water electrolysis OER oxygen production performance. Compared with the conventional constant voltage loading method, the microstructure obtained by the method of the present invention has better uniformity and better catalytic performance.

[0111] The present invention realizes precise control of acid etching and nanosheet growth by cyclic loading and controlling the waveform of the loading curve, wherein both acid etching and nanosheet growth require the diffusion of ions, and it is found through linear cyclic loading that controlling the etching time by different waveforms can effectively provide uniform diffusion time of ions, and this method can effectively inhibit local excessive corrosion or growth, thereby improving the uniformity of the microstructure of the electrode surface.

[0112] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a three-dimensional multi-scale electrode with a nanosheet microstructure, characterized in that: The following steps are involved: S1: Preparation of alloy specimens; S2: The alloy sample block is used as the working electrode, Ag / AgCl is used as the reference electrode, and the carbon rod is used as the counter electrode. The three-electrode system is connected through an electrochemical workstation and placed in an acid solution for electrochemical acid etching. The electrochemical acid etching adopts cyclic voltammetry, and the electrochemical acid etching process is controlled by adjusting four parameters in the cycle waveform: the peak voltage E1 of the working electrode relative to the reference electrode, the voltage change speed V1 of the working electrode, the loading time interval T1, and the number of cycles N1. S3: cleaning and drying the alloy sample after electrochemical acid etching to obtain a three-dimensional multi-scale electrode intermediate; S4: A three-dimensional multi-scale electrode intermediate is used as the working electrode, Ag / AgCl is used as the reference electrode, and a carbon rod is used as the counter electrode. The three-electrode system is connected through an electrochemical workstation and placed in an alkaline solution for alkaline growth. The alkaline growth is performed by linear sweep voltammetry. The growth rate of the alkaline growth and the distribution uniformity of the obtained nanosheets are controlled by adjusting four parameters in the cyclic waveform: the peak voltage E2 of the working electrode relative to the reference electrode, the voltage change rate V2 of the working electrode, the loading time interval T2, and the number of cycles N2. S5: cleaning and drying the three-dimensional multi-scale electrode intermediate after the alkali growth to obtain the three-dimensional multi-scale electrode.

2. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: The adjustment ranges of the four parameters in electrochemical acid etching are: the peak voltage E1 of the working electrode relative to the reference electrode is 1-2V, the voltage change rate V1 of the working electrode is 50-200mV / s, the number of cycles N1 is 10-100 cycles, and the loading interval time T1 is 1-30s.

3. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: The adjustment ranges of the four parameters in alkali growth are: the peak voltage E2 of the working electrode relative to the reference electrode is 1-2.5V, the voltage change rate V2 of the working electrode is 10mV / s, the number of cycles N2 is 100-1000 cycles, and the loading time interval T2 is 1-5min.

4. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: In step S2, the acid solution is a sulfuric acid aqueous solution with a concentration of 0.5 mol / L.

5. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: In step S4, the alkaline solution is a potassium hydroxide aqueous solution with a concentration of 1-5 mol / L.

6. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: The preparation method of the alloy sample block is as follows: according to the required metal active site type, the corresponding metal / alloy powder is selected, and at the same time, a sacrificial metal is selected according to the electrochemical corrosion potential, the sacrificial metal powder and the metal / alloy powder are mixed to obtain a powder raw material, and then the powder raw material is melted at high temperature in an argon atmosphere or prepared by 3D printing to obtain the alloy sample block.

7. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: The mass ratio of each element in the alloy sample block is Fe:Co:Ni:Cr:Al=17.5:19.7:38.2:16.1:8.

5.

8. The method for preparing a three-dimensional multi-scale electrode with a nanosheet microstructure according to claim 1, characterized in that: In step S3, the alloy sample after electrochemical acid etching is washed with deionized water, placed in an oven at 80° C. for 24 h for drying, and a three-dimensional multi-scale electrode intermediate is obtained.

9. The method for preparing a three-dimensional multi-scale electrode having a nanosheet microstructure according to claim 1, characterized in that: In step S5, the three-dimensional multi-scale electrode intermediate after alkali growth is washed alternately with deionized water and ethanol, and placed in an oven at 80° C. for 24 hours for drying to obtain the three-dimensional multi-scale electrode.

10. A three-dimensional multi-scale electrode with a nanosheet microstructure, characterized in that: Prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing a porous NiCu nanoneedle array catalyst

    CN112795952B